Analysis of internal indicators on performance of Islamic bank in Malaysia / Muhammad Hafiz Husaini Mohamed Kamal and Muhammad Fikri Jasni - Mohamed Kamal, Muhammad Hafiz Husaini; Jasni, Muhammad Fikri (Faculty of Business and Management, 2016)
There is not many research conducted to find the relationship between Islamic bank and new Islamic bank in Malaysia specifically. The variables used in the study are capital adequacy ratio (CAR), Financial Risk and liquidity. This study is referred to a research done in Malaysia which used the same variables. Panel Regression Random effect model were applied in this study to determine the relationship between the CAR, FR and LIQ towards Return on Asset (profitability) of Islamic bank in Malaysia. The results obtained in this study indicate each variable has positive relationship and negative relationship with the performance of Islamic bank.